Flexible piezoelectric energy harvester based on self-poled electroactive P(VDF-HFP)/(Fe2O3–PANI) composite film - Barman, Priti Sundar; Biswas, Avrajyoti; Ali, Salim; Roy, Debadrita; Roy, Mahendra Nath; Garain, Samiran; Adhikary, Prakriti (Frontiers in Energy Research, 2025)
Fabricating a piezoelectric generator for harvesting mechanical energy is a recent development that has exhibited great potential to enhance the piezoelectric coefficient, stretchability, flexibility, and integrability in small-scale (i.e., micro or nano) power supply and sensor systems for diverse applications. In this study, we report on the preparation of a copolymer composite P(VDF-HFP)/(Fe2O3–PANI) film, i.e., (‘hfp-fe-pn’), fabricated by incorporating ferric oxide (Fe2O3) and polyaniline (PANI) fillers with the host poly(vinylidene fluoride-co-hexafluoropropylene) [P(VDF-HFP)] copolymer that yields more than 99% electroactive β- and γ-phase formation, where a traditional electrical poling treatment was avoided. The nucleation and enhancement in the piezoelectric phase (i.e., β-phase) and the conversion of the degree of crystallinity (χc) in the P(VDF-HFP) copolymer are governed by the incorporation of these fillers, as revealed by the Attenuated total reflectance (ATR) and X-ray diffraction (XRD) analyses. Furthermore, the electrostatic interactions between the surface charges of Fe2O3 and the interfacial dipole–dipole interaction of the (=N–H)+ group of PANI fillers with –CH2−/−CF2– molecular dipoles in P(VDF-HFP) cooperate to stabilize the electro-active phases and enhance its piezoelectric properties. A piezoelectric generator (PEG) fabricated with the ‘hfp-fe-pn’ film shows an open circuit voltage output of ∼8 V and an output power of 10.3 nW. In addition, it generates enough power to instantly turn on commercial white/red light-emitting diodes (LEDs). The capacitor-charging capability of the PEG indicates its suitability for effectively harvesting mechanical energy from finger impact (a pressure amplitude of ∼14 kPa) and as an alternative in the area of self-powered energy harvesting devices.